Tren Self-Harm di Kalangan Generasi Zilenial - Meita Sulistiyo; Desta Alfia; Nadia Aulia Nadhirah (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2026)
This study discusses the phenomenon of self-harm, particularly Non-Suicidal Self-Injury (NSSI), which is prevalent among Generation Z adolescents. The method used is a systematic literature review by analyzing 25 scientific articles published in the last five years from the Scopus, SINTA, PubMed, and Google Scholar databases. The results of the study show that self-harm in adolescents is triggered by an inability to manage emotions, past trauma, social pressure, and the influence of digital media. Although not intended to end life, this behavior still has a serious impact on physical and mental health. Self-harm is also closely related to depression and an increased risk of suicide. Therefore, this study confirms that self-harm is not merely a behavioral problem, but a manifestation of complex psychopathology. Multidisciplinary interventions involving families, schools, and professionals are needed, as well as increased mental health literacy and digital content monitoring as preventive measures to reduce the prevalence of self-harm among adolescents.